Thermal distillation of bio oil from from fast pyrolysis of empty fruit bunch (EFB) and palm kernel shell (PKS) / Deana Qarizada - Qarizada, Deana (2019)
The palm oil industry generates abundance of oil palm biomass, such as empty fruit bunch (EFB) and palm kernel shell (PKS). Annually, around 30 million tonnes of biomass are produced in Malaysia. The objectives of this study are to characterize the raw material EFB, PKS and bio-oil, investigate the effect of temperature of distilled bio-oil, and compression of distilled bio-oil and bio-oil from PKS and EFB with liquid petroleum fuel. In this study, the pyrolysis of empty fruit bunch and palm kernel shell was investigated using a fixed bed reactor at 500 °C, and the thermal distillation of pyrolysis bio-oil were considered using a column reactor at three temperatures. Pyrolysis has received a lot of interest as it can convert biomass into liquid (bio-oil), gas, and solid products. Bio-oil can be used as a feedstock for various chemical well as fuel production, and heat and power generation. In this research, thermal distillation was performed to obtained ten distilled bio-oil (liquid fuel) at three temperatures 100 °C, 120 °C and 140 °C from fast pyrolysis bio-oil of the empty fruit bunch and palm kernel shell to elucidate the detailed characteristics of bio-oil and bio-oil fractions. The maximum bio-oil yield for EFB and PKS bio-oil were 54.50 wt % at 500 °C. Nitrogen flow rate of 200 mL/min and mass feeding was 6 kg/h. The maximum distilled bio-oil yield was 60-65 wt % at temperatures 100°C, 120 °C and 140 °C. The highest heating value obtained for PKS and EFB distilled bio-oil at 100°C, 120°C and 140 °C was 31.5 MJ/kg from PKS at 140 °C under sample number 10, and 28.5 MJ/kg from EFB at 140°C, also under sample number 10, which is about two times higher than pyrolysis bio-oil of PKS at 22 MJ/kg and EFB at 21 MJ/kg. The moisture content for both distilled bio-oils were arranged between 13-23.82 wt %, which is lower than the moisture content of the bio-oil. GC-MS and FTIR spectra indicated that phenol is a major component in both EFB and PKS distilled bio-oils, and most of the compounds were fused to the organic phase at high temperatures.